Origin of Prebiotic Organics and Oxygen on Earth. A case for the Pre-Photosynthetic and Carbonyl Sulfide Catalyzed Reduction of Carbon Dioxide by Water, Methane, Ammonia and Hydrogen sulfide. (JOURNAL OF ADVANCES IN PHYSICS, 2023)
It is estimated that the earth is about 4.5 billion years old and it is now believed that by 4.3 billion years ago, earth may have developed physico-chemical conditions suitable to support life, when its atmosphere consisted largely of water (H2O) vapor, nitrogen (N2), and carbon dioxide (CO2) with much smaller amounts of methane (CH4), carbon monoxide (CO), ammonia (NH3), hydrogen (H2), hydrogen sulfide (H2S) and other sulfur compounds like carbonyl sulfide (COS), and the earth had a reducing atmosphere without any free oxygen. The oldest known fossil records show that life came into being about 3.7 billion years ago. It is also believed that life proliferated and evolved in largest scale only after first aoxygenic photosynthesis by viruses and then oxygenic photosynthesis by plants produced large scale biochemocules and molecular oxygen (O2). But this necessitated a period of the evolution of primitive life forms like reprocing cells, which required enormous carbon-based prebiotic chemicals mediated by dialectical chance and necessity as is the case with later biological evolution. This had to involve the production within about a billion years, of specific prebiotic ingradients in enough quantities, in sufficient concentration in a limited, dynamic and physicochemically suitable localized evironment. But only the few primitive chemical compounds mentioned above, most abundent being H2O and CO2 , laready existing on earth, potentially could be source of enormous amount and variety of prebiotic chemicals necessary for the formation the  first reproducing cell. Based on the SET (Selective Energy Transfer Theory) developed by one of us (RL), we have reason to speculate for the first time that the carbonyl sulphide (COS) catalyzed reduction of CO2 by H2O and by other less abundant molecules like CH4, NH3 and H2S was the decisive prerequisite for the formation of  prebiotic chemical ingredients and for the chemical evolution of the first reproducing cell on Earth.